Ultrasonographic determination of bifurcation site of the tibial nerve at the tarsal tunnel - Donald Spears Wilcox; Antonio Tom Howard; Mark S. Mennemeier; Jacqueline Rainey; Charlotte Yates; Melissa Allen; Kevin D. Phelan (WFUMB Ultrasound Open)
Objective: Variability of Tibial nerve branching patterns with regard to the tarsal tunnel and malleolar-calcaneal axis has been established in a limited number of cadaveric studies with relatively few subjects. The current study used high-resolution ultrasonography to investigate tibial nerve branching variability, in-vivo, from a large number of healthy subjects. Methods: High resolution ultrasonography was used to map the course of the tibial nerve, to determine the bifurcation point into to medial and lateral plantar nerves with regard to the malleolar-calcaneal axis and the tarsal tunnel, and to classify them into one of five established branching patterns. The in-vivo, ultrasonography findings were then compared with findings from cadaveric studies. Results: The ultrasonography data for 156 feet (78 subjects-40 male, 38 female) of young, healthy individuals produced results similar to the cadaveric data with only small differences in each branching classification. Additionally, variation in the type of branching patterns between the left and right legs was observed in 23 % of the sample (i.e., 18 of 78 subjects). Conclusions: In-vivo, high-resolution ultrasound appears to be a valid approach for investigating anatomic variation of superficial nerves as the US data converge with those for cadaveric dissection. Further, not only were the percentages of branching pattern types replicated from earlier cadaveric studies, but also differences in the types of branching patterns between the left and right legs of the same subjects were observed in 23 % of the sample. A side-to-side difference of this type has not been previously reported. Finally, a decided advantage of using ultrasound to map nerve branching, when possible, is that it is easier to obtain a larger sample than in typical cadaveric studies. The current study more than doubled the number of specimens collected in previous cadaveric studies which greatly improves the external validity of our findings.